Impact of the etiology and special situations on waiting time on list and MELD of allocation in liver transplantation in the state of Paraná - Silveira, Fábio; Silveira, Fábio Porto; Silveira, Cassia Regina Sbrissia; Schulz, Ricardo Teles; Montero, Ana Sofia Jaramillo; Higa, Henrique Cesar (Brazilian Journal of Transplantation, 2020)
MELD system is settled in Brazil. The increasing MELD to the allocation, the influence of different etiologies, and the imbalance on the list, secondary to the granting upon special situations have raised discussions towards modernization of the system. In Brazil, each state is responsible by organizing the organ harvesting, resulting in a heterogeneous system. Purpose. To analyze the waiting time and MELD required for transplantation, the impact of different etiologies and granting upon special situations in the state of Paraná. Method. Analysis of 1248 adult liver transplants between 2010 and 2018, stratified according to the etiology, MELD and waiting time. Results. Age of 52+11.4 years. 112+197 days, 83.78% waiting time on the list of transplant cases below 6 months. Special situations were granted in 8.25% (n=103) of cases. There was no significant difference as to the waiting time on the list of the group with (110+107) and without (112+197) special situation. Transplant MELD (19.69+7.86), corrected MELD (22.24+6.42). Although being different among groups of etiology, MELD did not present growth pattern over time. Alcohol etiology (27.08%) and viral infections (23.56%) were the most frequent. 29.75% of transplants were performed with MELD above 75%. There was no change in the most common etiologies in this subgroup. Organ supply increased from 8.9pmp (2010) to 47.7pmp (2017). Conclusion. The impact of the progressive increase of MELD and waiting time on a list, secondary to the granting upon special situations is not observed on the waiting list of the State of Paraná. This discrepancy is probably secondary to the continuous growth almost parallel to the amount of donors and transplants performed.